2005
DOI: 10.1289/ehp.7652
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Health Assessment of Deltamethrin in a Malarious Area of Mexico: Environmental Persistence, Toxicokinetics, and Genotoxicity in Exposed Children

Abstract: We reported previously that children are exposed to deltamethrin in malarious areas. In the present work we explored the levels of this insecticide in soil samples and also obtained relevant toxico-kinetic data of deltamethrin in exposed children. Results show that, after spraying, indoor levels of deltamethrin in soil samples were higher than outdoor levels. The mean half-life estimated with these data was 15.5 days for outdoor samples and 15.4 days for indoor samples. Children’s exposure to deltamethrin was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 22 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…Although it is not possible to attribute exposure to specific pyrethroid insecticides from a single pathway using common urinary biomarkers such as PBA or trans-DCCA, the implementation of organic food substitution in the study design, coupled with the knowledge of pyrethroid insecticides use in the homes, allows us to draw the conclusion that CPES-WA children are simultaneously exposed to pyrethroid insecticides found in foods and from the use of pyrethroid insecticides in their daily environments. Although we did not measure environmental pyrethroid insecticides levels in this study, children's exposures to pyrethroid insecticides via dietary intake (Heudorf and Angerer, 2001;Schettgen et al, 2002;Ortiz-Perez et al, 2005;Becker et al, 2006), as well as from application of pyrethroid insecticides in the residential environment (Becker et al, 2006;Morgan et al, 2007;Tulve et al, 2007) have been reported previously. Pyrethroid insecticides and OP residues in the 24-h duplicate food samples that were collected in this study are being analyzed currently and will provide better characterizations of the dietary source of pyrethroid insecticides exposure.…”
Section: Discussionmentioning
confidence: 94%
“…Although it is not possible to attribute exposure to specific pyrethroid insecticides from a single pathway using common urinary biomarkers such as PBA or trans-DCCA, the implementation of organic food substitution in the study design, coupled with the knowledge of pyrethroid insecticides use in the homes, allows us to draw the conclusion that CPES-WA children are simultaneously exposed to pyrethroid insecticides found in foods and from the use of pyrethroid insecticides in their daily environments. Although we did not measure environmental pyrethroid insecticides levels in this study, children's exposures to pyrethroid insecticides via dietary intake (Heudorf and Angerer, 2001;Schettgen et al, 2002;Ortiz-Perez et al, 2005;Becker et al, 2006), as well as from application of pyrethroid insecticides in the residential environment (Becker et al, 2006;Morgan et al, 2007;Tulve et al, 2007) have been reported previously. Pyrethroid insecticides and OP residues in the 24-h duplicate food samples that were collected in this study are being analyzed currently and will provide better characterizations of the dietary source of pyrethroid insecticides exposure.…”
Section: Discussionmentioning
confidence: 94%
“…age, sex, muscle mass) can affect creatinine production (Boeniger et al, 1993). A recent report examining children's creatinine concentration as the children matured from preadolescence to adolescence clearly showed an increase in creatinine concentration with age (Ortiz-Perez et al, 2005). In addition, diurnal variations have been found with morning creatinine concentrations higher than evening creatinine concentrations (Barr et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…did not find an association between DDT/DDE floor dust concentrations and children’s blood levels (n = 20) (Herrera-Portugal et al, 2005). Further, Ortiz-Perez et al found that time since IRS with the pyrethroid delta-methrin corresponded to decreasing levels of two deltamethrin metabolites in children’s urine, but that longitudinal soil samples in the homes were not associated with these biomarkers (Ortiz-Pérez et al, 2005). In non-IRS communities, there is suggestive evidence that indoor dust levels of DDT contribute to serum levels (Davies et al, 1975), but other studies have not found an association with DDT floor dust levels and serum concentrations (Roosens et al, 2010; Ali et al, 2014; Buckley et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Although the benefits of decreased malaria infection are clear (Mabaso et al, 2004; Kim et al, 2012; West et al, 2014), the use of IRS for malaria control has contributed to uniquely high insecticide exposure in sprayed communities (Ortiz-Pérez et al, 2005; Aneck-Hahn et al, 2007; Channa et al, 2012; Bouwman et al, 2006; Sereda et al, 2009; Van Dyk et al, 2010) and uptake via home contamination is hypothesized to be a significant source of insecticide exposure (Channa et al, 2012; Van Dyk et al, 2010). In developed countries, house dust is a common environmental medium collected to assess long-term indoor chemical exposures because insecticides and other pollutants persist indoors due to reduced degradation from sunlight, moisture, and microorganisms (Lioy et al, 2002; Butte and Heinzow, 2002; Roberts et al, 2009).…”
Section: Introductionmentioning
confidence: 99%